2019
DOI: 10.1148/ryai.2019180022
|View full text |Cite
|
Sign up to set email alerts
|

Automated CT and MRI Liver Segmentation and Biometry Using a Generalized Convolutional Neural Network

Abstract: To assess feasibility of training a convolutional neural network (CNN) to automate liver segmentation across different imaging modalities and techniques used in clinical practice and to apply this technique to enable automation of liver biometry. Materials and Methods: A two-dimensional U-Net CNN was trained for liver segmentation in two stages by using 330 abdominal MRI and CT examinations. First, the neural network was trained with unenhanced multiecho spoiled gradient-echo images from 300 MRI examinations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 36 publications
1
82
2
5
Order By: Relevance
“…Despite this inherent limitation, we consider the two-dimensional volume measurement to be a practical method since processing three-dimensional volume data requires more time, higher computational capacity, and larger data storage capacity and may potentially increase the need for operators' correction in cases of inaccurate segmentation results in contrast to our approach. Thus, most of the previous studies involving volume measurement of the liver and spleen have utilized two-dimensional CT images (18,(29)(30)(31)(32).…”
Section: Kjronlineorgmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this inherent limitation, we consider the two-dimensional volume measurement to be a practical method since processing three-dimensional volume data requires more time, higher computational capacity, and larger data storage capacity and may potentially increase the need for operators' correction in cases of inaccurate segmentation results in contrast to our approach. Thus, most of the previous studies involving volume measurement of the liver and spleen have utilized two-dimensional CT images (18,(29)(30)(31)(32).…”
Section: Kjronlineorgmentioning
confidence: 99%
“…First, our algorithm was developed and validated using portal venous phase CT images. The application of our algorithm to other CT images may require further training of the algorithm using additional training data through transfer learning (18,26). Second, our algorithm only provides whole liver segmentation.…”
Section: Kjronlineorgmentioning
confidence: 99%
“…Liver segmentation has direct clinical applications, including liver volume measurement, which is important in pre-operative planning for liver resection (46,47), determination of the radiation dose in liver tumor radioembolization, and measurement of quantitative indices such as the proton density fat fraction (PDFF) from the whole liver (48). Notably, however, liver segmentation is labor-intensive and time-consuming, which limits its usage in clinical practice.…”
Section: Liver Segmentationmentioning
confidence: 99%
“…All of these studies reported high performance values in liver segmentation, with the reported DSS values ranging from 0.92 to 0.95 (50)(51)(52)(53)(54). Recently, Wang et al (48) demonstrated the feasibility of generalized CNN, which can be used for liver segmentation on CT scans and various MRI sequences using the transfer learning technique. They reported DSS values ranging from 0.92 to 0.95 for liver segmentation on CT and MR images.…”
Section: Liver Segmentationmentioning
confidence: 99%
“…Automatic medical image segmentation approaches that are introduced in the last two decades have been the most successful methods for medical image analysis. The feasibility of a CNN to be generalized to perform liver segmentation across various imaging strategies and modalities is used in [9]. Patrick et al [2] presented a method to automatically segment liver and lesions in CT and MRI abdomen images using cascaded fully convolutional neural networks (CFCNs) enabling the segmentation of large-scale medical trials and quantitative image analysis.…”
Section: Introductionmentioning
confidence: 99%